Cloning, expression, and localization of Tekt1 in sterile allotriploid crucian carp - Shuxin Zhang; Liran Zhang; Faxian Yu; Xinge Ouyang; Haoxiang Yang; Qining Zuo; Yujie Huang; Xin Chen; Shengnan Li; Min Tao (Reproduction and Breeding)
Tektins (TEKTs) are constitutive proteins of microtubules associated with flagella, cilia, basal bodies, and centrioles. As one of the testis-specific candidate markers, Tekt1, the first identified member of the TEKT family in mammals, is intimately linked to the formation of sperm flagella and may play a pivotal role in flagellar stability and sperm motility. However, studies on Tekt1 in fish species are still relatively understudied. In this study, the full-length cDNAs of Tekt1 were respectively 1727 bp and 1696 bp in allotriploid crucian carp and diploid red crucian carp, which both comprised a 1209 bp open reading frame (ORF) encoding 402 amino acids. Conversely, the diploid common carp possessed a cDNA length of 1771 bp, characterized by a 1218 bp ORF encoding 405 amino acids. The Western blot analysis revealed that the expression level of Tekt1 protein in the testes of sterile allotriploid crucian carp was markedly decreased in comparison to that of fertile diploid red crucian carp during both pre-spermiation and spermiation periods. The immunohistochemistry analysis revealed abnormalities in the spermiogenesis of allotriploid crucian carp, showcasing a distinctive localization pattern of Tekt1 exclusively present in spermatids, in contrast to diploid red crucian carp, where Tekt1 was detected in both spermatids and spermatozoa. Taken together, these findings suggested differential expression of Tekt1 during spermiogenesis between allotriploid and diploid species, and indicated that the decreased expression of Tekt1 protein in allotriploid crucian carp might be associated with male sterility. Furthermore, these results pave the way for further exploration of reproductive characteristics in male allotriploid crucian carp and offer a theoretical foundation for future research on polyploid breeding.